2021
DOI: 10.1002/eji.202048960
|View full text |Cite
|
Sign up to set email alerts
|

PD‐1‐specific “Blocking” antibodies that deplete PD‐1+ T cells present an inconvenient variable in preclinical immunotherapy experiments

Abstract: Therapeutic antibodies blocking PD‐1‐/PD‐L1 interaction have achieved remarkable clinical success in cancer. In addition to blocking a target molecule, some isotypes of antibodies can activate complement, NK cells or phagocytes, resulting in death of the cell expressing the antibody's target. Human anti‐PD‐1 therapeutics use antibody isotypes designed to minimize such antibody‐dependent lysis. In contrast, anti‐PD‐1 reagents used in mice are derived from multiple species, with different isotypes, and are not e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…IgG4. 27,65 As mentioned previously, we have reported that active immunization of mice with the mimotope from mouse PD1 results in an increased antitumor effect. This effect, however, was shown to be associated with a marginal level of the induced mimotope/PD-1-specific antibodies which was clearly lower than the level of the passively transferred respective antibody.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…IgG4. 27,65 As mentioned previously, we have reported that active immunization of mice with the mimotope from mouse PD1 results in an increased antitumor effect. This effect, however, was shown to be associated with a marginal level of the induced mimotope/PD-1-specific antibodies which was clearly lower than the level of the passively transferred respective antibody.…”
Section: Discussionmentioning
confidence: 68%
“… 23 , 24 , 25 In addition, the ambiguous interactions between Fcγc and antibodies are a matter of concern in ICI therapy and require careful selection of antibodies with suitable isotypes. 26 , 27 Moreover, continuous target inhibition as a result of the therapeutic mAbs’ long half-lives may also contribute to irAEs.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguing new data demonstrates the variable impact of anti-PD-1 clones routinely utilized in murine preclinical studies. 49 Particularly, this work shows the Armenian Hamster IgG G4 clone to promote depletion of PD-1+ T cells in comparison to the Rat IgG2a RMP1-14 clone 49 (these clones were used in 4/16 and 7/16 of the studies discussed here, respectively; Table 1 ). Furthermore, there is evidence to suggest that the RMP1-30 clone, used in one of the 16 studies explored here, 33 does not actually block the interaction of the PD-1 molecule with PD-L1 and PD-L2 like the J43 and RMP1-14 clones do.…”
Section: Approachmentioning
confidence: 83%
“…The ability of anti-PD-1 antibody F(ab) 2 to bind PD-1 was evaluated by flow cytometry. EL-4 mouse lymphoma cells, reported to express high level of PD-1 [29], were stained with 10 µg/mL anti-mouse PD-1 antibody (clone RMP1-14) (BioXCell, West Lebanon, NH, USA) or anti-mouse PD-1 antibody F(ab) 2 for 30 min at 4 • C. To prevent nonspecific binding to mouse Fc receptors, the cells were also incubated with a purified rat anti-mouse CD16/CD32 monoclonal antibody (eBioscience-Thermo Fisher Scientific Inc., Waltham, MA, USA). After washing, the cells were incubated with FITC-conjugated anti-rat IgG (H+L) antibody, mouse serum adsorbed (KPL, SeraCare Life Sciences, Milford, MA, USA) for 30 min at 4 • C. Samples were then acquired using a BD FACSCelesta™ Cell Analyzer (BD Biosciences, San Jose, CA, USA) and analyzed with FlowJo software (FlowJo LCC, Ashland, OR, USA).…”
Section: Flow Cytometry Analysismentioning
confidence: 99%